CALCULATION OF PIPES SINGLE FORCED CONVECTION - Gorobets, V. (Energy and Automation, 2016)
Using the method of calculation of heat transfer in pipe channels for thenonisothermal surface the numerical calculation of heat transfer for single tube is conducted and distributions of local heat transfer coefficient in tube channel are received. A comparison the results of numerical calculation with the results of calculation using of simplified modalities is conducted and the errors that occur is found.